2006
DOI: 10.1159/000096593
|View full text |Cite
|
Sign up to set email alerts
|

Hypergastrinemia Is Associated with Increased Risk of Distal Colon Adenomas

Abstract: Background/Aims:Helicobacter pylori infection is a recognized cause of hypergastrinemia, but the association of blood gastrin levels with colonic adenomas (CAs) is controversial. The aim of this study is to investigate if hypergastrinemia, H. pylori infection and/or cagA protein are risk factors for CAs. Methods: In this prospective case-control study, fasting serum samples from 78 consecutive patients with CAs and 78 demographically matched colonoscopy-negative controls were assayed for anti-H. pylori immunog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 71 publications
1
62
0
2
Order By: Relevance
“…A limited number of previously conducted epidemiological studies investigating the correlation between colorectal neoplasia and gastrin, demonstrated inconsistent results. More specifically, certain studies indicated positive correlations (32), while others including a recent large-scale nested case-control study, determined no such correlation (25,33). The differences in results reported in these studies might be attributable to the fact that most commercially available assays for gastrin detect the mature, fully-amidated form of the hormone, while gastrin precursors, such as progastrin or glycine-extended gastrin, are considered to act as more important promoters of colorectal carcinogenesis (2)(3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of previously conducted epidemiological studies investigating the correlation between colorectal neoplasia and gastrin, demonstrated inconsistent results. More specifically, certain studies indicated positive correlations (32), while others including a recent large-scale nested case-control study, determined no such correlation (25,33). The differences in results reported in these studies might be attributable to the fact that most commercially available assays for gastrin detect the mature, fully-amidated form of the hormone, while gastrin precursors, such as progastrin or glycine-extended gastrin, are considered to act as more important promoters of colorectal carcinogenesis (2)(3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…Because H. pylori increases gastrin levels, an association between H. pylori infection and colorectal neoplasia has frequently been sought. Although the findings are still debated, H. pylori infection appears to increase the risk of colonic adenomas, particularly in the more distal colon (31,36,85,169,223). The postulated mechanism is similar to that derived for gastric cancer: H. pylori-induced hypergastrinemia influences precancerous lesions toward malignant transformation.…”
Section: Effects Mediated Through Human Gastrin Hormonementioning
confidence: 96%
“…There are several speculations about this association. It has been assumed that H. pylori infection of the gastric mucosa leads to increased levels of serum gastrin, which may act as a growth-promoting hormone on the colon mucosa [43,44]. H. pylori could act on the colon mucosa itself and affect polyp growth or promote the development of mucosa dysplasia.…”
Section: Discussionmentioning
confidence: 99%